3D pictorial structures for multiple human pose estimation - Belagiannis, Vasileios; Amin, Sikandar; Andriluka, Mykhaylo; Schiele, Bernt; Navab, Nassir; Ilic, Slobodan (Proceedings of the IEEE Computer Society Conference on Computer Vision and Pattern Recognition, 2014)
In this work, we address the problem of 3D pose estimation of multiple humans from multiple views. This is a more challenging problem than single human 3D pose estimation due to the much larger state space, partial occlusions as well as across view ambiguities when not knowing the identity of the humans in advance. To address these problems, we first create a reduced state space by triangulation of corresponding body joints obtained from part detectors in pairs of camera views. In order to resolve the ambiguities of wrong and mixed body parts of multiple humans after triangulation and also those coming from false positive body part detections, we introduce a novel 3D pictorial structures (3DPS) model. Our model infers 3D human body configurations from our reduced state space. The 3DPS model is generic and applicable to both single and multiple human pose estimation. In order to compare to the state-of-the art, we first evaluate our method on single human 3D pose estimation on HumanEva-I [22] and KTH Multiview Football Dataset II [8] datasets. Then, we introduce and evaluate our method on two datasets for multiple human 3D pose estimation.
CRIS-Team Scopus Importer:2022-07-19
Keywords: 3D pose estimation; human pose estimation; pictorial structures